2019
DOI: 10.5713/ajas.17.0920
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc-bearing palygorskite on rumen fermentation in vitro

Abstract: These results suggest that the addition of Zn-Pal can improve the rumen fermentation, especially when adding 0.2% Zn-Pal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…According to the observations of this study, the addition of nano-ZnO on the protein source had no effect on gas production after 24 h. However, reduction and the tendency to decrease in the volume of gas production after 24 h of incubation in other study [37] are also shown. This tends to decrease with increasing the nano level, unlike results researchers [27,28] , which was up high enough so that the inhibitory effect on the activity of rumen microorganisms was shown. Between sources of animal protein, POM and BM at any of the incubation times was not affected by the addition of ZnO nanoparticles, but adding ZnO nanoparticles to FM except the first 2 h of incubation at other times had significantly effect on increasing gas production.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…According to the observations of this study, the addition of nano-ZnO on the protein source had no effect on gas production after 24 h. However, reduction and the tendency to decrease in the volume of gas production after 24 h of incubation in other study [37] are also shown. This tends to decrease with increasing the nano level, unlike results researchers [27,28] , which was up high enough so that the inhibitory effect on the activity of rumen microorganisms was shown. Between sources of animal protein, POM and BM at any of the incubation times was not affected by the addition of ZnO nanoparticles, but adding ZnO nanoparticles to FM except the first 2 h of incubation at other times had significantly effect on increasing gas production.…”
Section: Discussioncontrasting
confidence: 58%
“…Also, in an in vitro test using ZnO nanoparticles in the diet improve rumen bacterial growth and increasing the efficiency of energy intake in the diet [27] . In other experiment [28] amount of in vitro gas produced over 144 h of incubation there was no significant difference in treatments containing zinc at levels 20 and 40 ppm with control.…”
Section: Introductionmentioning
confidence: 99%
“…Zn is also involved in a wide assortment of physiological processes, so nutrient digestibility may be affected by supplemental Zn, which is incorporated into enzymes throughout the body and is critical for most metabolic processes in ruminants ( 47 ). Zinc in the diet of ruminants can substantially influence ruminal fermentation ( 48 , 49 ). Low doses of zinc (20–70 mg Zn/kg diet) only weakly affect ruminal fermentation ( 4 , 10 ), but higher doses (250–1,142 mg Zn/kg diet) can affect ruminal protozoal populations and protein degradation ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zn is also involved in a wide assortment of physiological processes; therefore, nutrient digestibility may be affected by supplemental Zn, which is incorporated into enzymes throughout the body and is critical for most metabolic processes in ruminants [46]. It is known that zinc in the nutrition of ruminants can signi cantly in uence ruminal fermentation [47,48]. While low doses of zinc (20-70 mg Zn/kg diet) have a weak effect on rumen fermentation [4,10], higher doses (250-1142 mg Zn/kg diet) can affect the rumen protozoal population and protein degradation [49].…”
Section: Discussionmentioning
confidence: 99%